EFEKTIVITAS PENERAPAN BRAIN GYM UNTUK MENINGKATKAN MINAT BELAJAR - Morgani, Layung; Asrori, Muhammad; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractLearning interest is an essential foundation for students to conduct proper learning activities. The interest in learning in students indicates that there are a great passion and desire for students towards learning delivered by the teacher. Brain Gym is one method in the form of interactive media that can be used to increase student interest in learning. This study was conducted to determine the effectiveness of the Brain Gym to increase students' learning interest. This research was conducted by obtaining learning interest data before and after the implementation of Brain Gym. The study was conducted through experimental research methods in grade VII students of Pontianak Islamic Middle School Ashabul Kahfi, with a population of 80 people, and a sample of 40 people. The research design used was pre-experimental research in the form of one group pretest-posttest design. The average score of students before applying Brain Gym is 151.25 with a high category, while the average score of students after applying Brain Gym is 175.10 with a very high category. The effect size of Brain Gym is 1,532 with a high category. Therefore, the implementation of the Brain Gym method is effective in increasing students' learning interest.Â Keywords: Â Brain Gym, Interest In Learning, Pre-ExperimentalÂ